Predicting Financial Well-being Using Demographic Profile: A Study Proposed On Students Of Public Universities In Sabah, Malaysia - Nelson Lajuni; Imbarine Bujang; Abdul Aziz Karia (Universiti Malaysia Sabah, 2016)
This paper aims to make a specific contribution to the issue of financial well-being among students of public universities in Sabah. The discussion on this paper aims to debate the importance of the policymakers to continue to learn, change and adapt to challenges within the internal and external spectrums of the environment to respond to the expectations of different stakeholders. Therefore, this paper tends to seek evaluating the relationship between demographic profile and financial well-being to scrutinize on whether public universities students are prepared and equipped with financial knowledge. First, the literature on financial well-being is reviewed with a view to the identification of useful models and concepts. The paucity of reference to financial well-being in that literature is noted especially here in Malaysia. The discussion will look into issues faces financial well-being among public universities students in Sabah. Finally, nonlinear autoregressive with external (NARX) network is proposed and recommended to be used to examine on how the demographic profile affects financial knowledge and financial well-being. We have developed a conceptual framework for demographic profile and shown its relationship on financial knowledge and eventually to financial well-being. A key finding of our study is that demographic profile is a multi-faceted construct. The demographic profile measurements permit sharing with policymakers what researchers have learned about successful of financial knowledge that eventually translated into financial well-being. It presents an ideal approach whereby policymakers are confronted with the latest research findings concerning the determinants of financial well-being, how they can applied, how the policymakers can attempt to increase its chances of improving the financial education in Malaysia. In return, it will permit researchers to study “cases” over time and to gain greater depth of knowledge concerning not just the presence of demographic profile success-related characteristics, but also an understanding of how policymakers move the public universities students toward financial knowledge and eventually to financial well-being by adjusting their levels of readiness.